Construction of Ecological Security Evaluation Index System for Hengshui Lake National Nature Reserve Based on the Pressure-State-Response Model (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Ecological security is crucial for national security, human survival, and sustainable development. Thus, this study aims to establish an Ecological Security Evaluation Index System for Hengshui Lake National Nature Reserve in China based on the Pressure-State-Response (PSR) model. This reserve is a critical habitat for various wildlife species and provides essential ecosystem services to surrounding communities facing ecological issues, such as transitional development and accelerated urbanisation. The PSR model was chosen in this study because this tool provides a comprehensive and complex framework for assessing ecological security by considering three key components: Pressure, State, and Response. Three pressure components have been selected as indicators: Population, population density, and natural population growth rate. Meanwhile, eight condition parameters were included as the state indicator: Precipitation, precipitation pH, eutrophication, comprehensive water quality pollution index, chemical oxygen demand (COD), total phosphorus, fluoride, and permanganate index. Finally, the proportion of the tertiary industry, residents’ per capita disposable income, energy conservation and environmental protection expenditures, education expenditure, social security expenditures, and wetland environmental protection awareness were the response indicators considered in this study. The findings indicated that the ecological security evaluation index of Hengshui Lake between 2016 and 2022 increased from 0.203 to 0.756, whereas the ecological security level transitioned from unsafe to safe.
Keywords: wetland conservation; sustainability indicator; indicator system; combined weighing method